Active mobility demand and active travel behaviour - Teow, Alicia Chai Tze (2018)
In Singapore, various measures such as providing more cycling paths, sheltered walkways and campaigns are put in place to encourage more people to adopt active modes of transport – mainly walking and cycling. In order to bring these measures to their full potential, information of critical trends and travel behaviour of people should be established. This study aims to identify trends and travel behaviour of the people in Jurong Lakeside District (JLD). As this project is a dual student project, analysis will be divided into two reports- based on age group (covered in this report) and based on trip purposes (Chua, 2018). Relevant information from Households Interview Travel Survey (HITS) data from year 2012 is used for this study. Quantitative method of analysis is adopted to analyse the trends and travel behaviour. Trends such as peak hour period and trip duration are studied, and travel behaviour such as types of transport modes used, number of trip stages, first last mile (FLM) trip stage durations are studied. Special interest is placed in trips and trip stages that are performed by active modes of transport and short trip stages that are potential shifts to walking and cycling. Based on findings, alternatives to further increase active mobility rates in line with the Singapore “car-lite” goal is proposed. Findings from the study reveal that the peak hour period for age groups are staggered, participants aged 6-19 years’ old travelling at 6:00-6:59am, participants aged 20-39 years old travelling at 8:00-8:59am, participants aged 40-54 years’ old travelling at 7:00-7:59am. Government measures can suit each age group with different trip purpose according to their travel time. Moreover, the study reveals that younger participants (6-14 years’ old) and elder participants (above 70 years old) usually complete shorter duration (distance) trips and have higher percentage of trips completed on foot. The higher tendency of undertaking full (from origin to destination) walking trips could be due to the short distance of the trips. The most common mode of transport in general was found to be public buses. Thus, government measures can be made targeting public buses users to encourage them to use active modes of transport instead, especially since public bus travel time, especially during peak periods, are comparable with active modes of transport trip duration. The findings of this study can be utilised in planning and implementing various policies to complement existing government measures to encourage the use of active modes of transport.